Emotion and learning in digital games: a case study with children from an NGO in Parnamirim, Brazil - Uehara, Misa; Da Silva Santa Rosa, José Guilherme (InfoDesign, 2024)
This study examined the principles related to analyzing ludic schemes in digital games, with a focus on collecting data about the learning perception and emotions of children (aged 7-11) facing social vulnerability in Parnamirim, Brazil. Two focus group sessions were conducted, one of which involved a questionnaire. After data interpretation through content analysis, it was concluded that children perceive emotions and recognize multiple intelligences during their interaction with the reported games, identifying specific mechanics and moments associated with these emotions. As a secondary finding, it was observed that the adapted session, featuring illustrative cards developed based on previous responses from the children, showed superior performance in questions about learning. The connection between learning and individual engagement, with engagement being intrinsically linked to emotions, is evidenced through the participants’ own perceptions. It was concluded, through literature and practical demonstration that this interaction exists and can be beneficial for learning different skills, with the collection of such data being important for prioritizing the needs of individuals in design and education. The adaptation with cards, tailored to the group’s needs, fosters greater interaction and involvement, aligning with the constructivist notion of children’s participation in research, knowledge to which this study aims to contribute.